Analytical Method Development and Validation of RP-HPLC Method for Estimation of Imeglimin in Bulk and Pharmaceutical Dosage Form - P. Khaire, Aniket.; U. Barge, Vijaya. (Journal of Neonatal Surgery, 2025)
A new technique for evaluating the oral antidiabetic medication Imiglimin hydrochloride has been created and verified using High-Performance Layer Chromatography (HPLC) for both tablet and bulk forms. Acetone is used as a mobile phase in the procedure. Formic acid, toluene, and methanol in particular ratios. Drug absorbance is substantial at 240 nm, where chromatographic separation was accomplished on silica gel TLC plates using densitometry scanning. The findings of the validation, which adhered to ICH Q2R1 recommendations, were good in terms of linearity, accuracy, precision (both intra- and inter-day) and robustness. The new class of oral antidiabetic drugs known as "glimins," which contain tetrahydrotriazine, is called Imeglimin hydrochloride (IMEG. HCL) and is used to treat type 2 diabetes (T2D). It is the first of its kind to be approved as an anti-diabetic medication. In addition to improving muscle glucose uptake and restoring regular insulin secretion, it is an inhibitor of oxidative phosphorylation1. Using a Hypersil ODS C18 (150 x 4.6mm 5µ) Column and an isocratic mobile phase of Buffer pH 3.5 and Methanol (80:20)) pH6.0, a reverse phase HPLC technique was created and verified for the quantitative measurement of Imeglimin hydrochloride at a flow rate of 1 ml/min. The procedure complied with ICH recommendations Q2 (R1) for validation. and was discovered to be robust, precise, accurate, and specific. It may be used effectively for routine analysis of Imeglimin hydrochloride in pharmaceutical dosage forms as well as in bulk.